Reversão de bens nas concessões de serviço público - Guimarães, Felipe Montenegro Viviani (2023)
This thesis deals with the reversion of assets in the ambit of public service concessions. It is justified for many reasons, especially because: (i) several concessions granted in the 1990s, with a term of thirty years, will soon expire, if not extended, giving rise to the reversion of assets; and (ii) many public service concessions granted recently are undergoing or will undergo the re-bidding process, which also involves reversion. Therefore, the theoretical and practical interest in the reversion institute is already high in our country, and tends to increase in the coming years. The objective of this thesis is divided into: (i) a general objective; and (ii) a specific objective. The first one is to determine, in the best possible way, the greatest possible number of general characteristics of the legal institute of reversion. The second is to answer the following question: which is the legal consequence of the non-fulfillment, by the Granting Authority, of the obligation to pay, previously, to the public service concessionaire, the indemnity owed in reason of the reversion, in case of termination of the concession due to the advent of the contractual term? And the research hypothesis is that the legal consequence of non-fulfillment of this obligation is the automatic extension of the concession, until the payment of the indemnity owed to the concessionaire or the satisfaction of its credit through the exploitation of the public service, whichever occurs first. Thus, this thesis is divided, basically, into two parts: the first one, dedicated, more specifically, to the general objective of this work; the second, exclusively, to its specific objective. The approach method of the theme is the inductive, for the general objective, and the deductive, for the specific. And the research method is the bibliographic, for both objectives. Finally, the main conclusion of this thesis is that the legal consequence of the nonfulfillment, by the Granting Authority, of the obligation to pay, previously, to the public service concessionaire, the indemnity owed in reason of the reversion, in case of termination of the concession due to the advent of the contractual term, is the automatic extension of the concession, until the payment of this indemnity or the satisfaction of the concessionaire credit through the exploitation of the public service, whichever occurs first, but that as long as certain assumptions are verified; to know: (i) the Granting Authority has not paid, by the end of the concession contract, at least the indemnity amount uncontroversial between the parties; and (ii) the public service concessionaire has acted in a diligent manner in relation to the reversion, which is verified when it has acted proactively in relation to the initiation and instruction of the reversion process. In this way, the research hypothesis is confirmed, but with depurations